Economic Value of Children and Fertility Preferences in a Fishing Community in Southern Ghana - Teye, J.K. (Springler, 2010)
Although anecdotal evidence suggests that fertility levels in fishing communities, in Ghana, are very high, the influence of economic and cultural factors on fertility preferences in such communities has not been adequately explored. This article examines the fertility preferences of men and women living at Akplabanya, a fishing community in Ghana. Data were collected from a sample of 354 respondents. The findings of the study show that demand for labour, expectations of long term security, and gendered power relations have contributed to high fertility levels and preferences in the study area. It has been concluded that significant fertility decline in the area will only occur when fertility preferences of men have changed. Family planning programmes must therefore target both men and women. Improving economic status of women will also go a long way to bring about fertility transition in rural communities in Ghana.
Keywords: Economic value of children, Fertility preferences , Cultural values , Fishing communities, Ghana